The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s100670070051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cerebrospinal Fluid for the Presence of Anticardiolipin Antibodies (aCL) in NP-SLE Patients

Abstract: Many neurological or psychiatric manifestations of SLE (NP-SLE) are related to the presence of anticardiolipin antibodies (aCL) in the patient's sera. The aim of this study was to evaluate the presence of aCL in cerebrospinal fluid (CSF) in SLE patients with NP features. Fifteen SLE patients were studied, all with NP features. CSF was evaluated for intrathecal IgG synthesis, oligoclonal IgG, and blood-brain barrier impairment. Sera and CSF were tested by ELISA for the presence of aCL-IgG and aCL-IgM with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Although the former possibility is viable when serum antibodies (originally directed towards peripheral antigens) are considered, our studies and clinical evidence (Lai and Lan, 2000) suggest that neuroactive antibodies are synthesized intrathecally. Similar to the present lack of discriminative value in the MRL model, in some clinical studies ACA could not be detected in the CSF of patients with NP-SLE, even when found in their sera (Jedryka-Goral et al, 2000). With respect to pro-inflammatory cytokines measured in the present study, we infer that they do not play a key role in cytotoxicity towards proliferating cells.…”
Section: Discussionsupporting
confidence: 81%
“…Although the former possibility is viable when serum antibodies (originally directed towards peripheral antigens) are considered, our studies and clinical evidence (Lai and Lan, 2000) suggest that neuroactive antibodies are synthesized intrathecally. Similar to the present lack of discriminative value in the MRL model, in some clinical studies ACA could not be detected in the CSF of patients with NP-SLE, even when found in their sera (Jedryka-Goral et al, 2000). With respect to pro-inflammatory cytokines measured in the present study, we infer that they do not play a key role in cytotoxicity towards proliferating cells.…”
Section: Discussionsupporting
confidence: 81%
“…A stronger association between aPL and neurological disorders might be easier to establish if aPL are sought and detected in the cerebral spinal fluid (CSF) of patients experiencing neurologic symptoms. Historically, scarce reports of aPL in CSF are limited mostly to IgG and IgM anticardiolipin (aCL) detection (Marchiorri, 1990;Lolli et al, 1991;Wang et al, 1992;Gallo et al, 1994;Yeh et al, 1994;Martinez-Cordero, 1997;Jedryka-Goral et al, 2000;Lai and Lan, 2000;Baraczka et al, 2002). Rarely are IgA aCL sought (Wang et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the leakage of the BBB was believed to be the only mechanism allowing peripheral autoantibodies to enter the brain parenchyma and start an immune response to neuronal components. Goral and colleagues studying patients affected by NPSLE have discovered that the presence of aCL, commonly associated with thrombosis risk in patients with SLE [ 63 ], is not associated with BBB disruption or intrathecal antibody production [ 64 ]. These results suggest that the disruption of BBB is not due to prothrombotic events, but rather it is related to the overexpression of proinflammatory cytokines promoting the infiltration of leukocytes within the CNS (Fig.…”
Section: Neuropsychiatric Systemic Lupus Erythematosusmentioning
confidence: 99%